Peningkatan Kompetensi Membaca Teks Berbahasa Arab melalui Metode Qiraah Mata Pelajaran Bahasa Arab di MTs Negeri 8 Karangmojo - Siti Khotiah (Jurnal Pendidikan Madrasah, 2020)
This research aims to describe the implementation of professional method in improving students ' competency in reading Arabic text in class VII-A students at MTs Negeri 8 Karangmojo, in the even semester, school year 2018/2019. The study uses action research methods in two cycles. The results showed increased student reading competence gained through several activities, namely: 1) demonstrating reading, saying letters, words (Mufrodaat), sentences, and phrases aloud and repeatedly; 2) Habituation of reading Al-Quran (Tadarus) with teacher monitoring; and 3) memorization deposits. The ability to read students on Arabic text increases on each cycle with an average of 28 percent of the 26 students; 53.85% in good criteria, 38.46% in very good criteria, and 7.69% in less good criteria. Qiraah method can improve the students ' ability to read Arabic text.